2008
DOI: 10.1007/s10518-008-9098-x
|View full text |Cite
|
Sign up to set email alerts
|

Shear effects on hollow section piers under seismic actions: experimental and numerical analysis

Abstract: Shear effects are often a very important issue on the seismic behaviour of piers, particularly for hollow section bridge piers. In fact, for this type of piers the cyclic response is similar to that of a structural wall in which both the transverse reinforcement ratio and the detailing can play an important role on its performance, even likely to be determinant in terms of the failure mechanism. On the other hand, codes and design guidelines are usually very conservative concerning shear capacity in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 6 publications
1
24
0
Order By: Relevance
“…At the same time, it was identified that this evolution of the cost is potential, being translated by equation (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it was identified that this evolution of the cost is potential, being translated by equation (1).…”
Section: Discussionmentioning
confidence: 99%
“…This paper focus on the analysis of damages on hollow piers due to the seismic action, proposing a methodology to characterize the limit states of damage under the perspective of the physical behaviour. To establish a correspondence between physical damage states and structural parameters, a set of results of quasi-static experimental tests was analysed, in hollow piers of reinforced concrete subject to cyclic loading [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Only quite recently, attention has been paid to experimental cyclic response of hollow columns: relatively few experimental studies, especially if compared with columns with solid cross section, are available in literature. Some of the existing studies [5][6][7][8] highlighted that the lateral response of existing (poorly detailed) hollow RC piers is characterized by high shear deformations, comparable to ones typical of RC walls, which may represent also a considerable portion of global top displacement. Calvi et al [5] observed that fiber models, good in capturing flexural response, needed corrections in order to include some stiffness reduction due to shear deformability.…”
Section: Introductionmentioning
confidence: 99%
“…Calvi et al [5] observed that fiber models, good in capturing flexural response, needed corrections in order to include some stiffness reduction due to shear deformability. Delgado and his colleagues [6][7][8] noted that shear deformation of hollow piers cannot be captured with typical models, based on fiber or plastic hinge approaches; therefore, they adopted a more advanced numerical tools, with 3D finite elements and complex constitutive models, to adequately reproduce the experimental response of poorly detailed RC columns, both in terms of load and deformability.…”
Section: Introductionmentioning
confidence: 99%
“…The test setup characteristics and more detailed results are available in previous reports [1][2][3][4]. This set of specimens was based on square piers tested at the Laboratory of Pavia University, Italy [5,6], consisting on hollow section RC piers with 450mm x 450mm exterior dimensions and 75mm thick walls, and is being tested in order to understand the influence of the cross section geometry of rectangular hollow piers on the cyclic behavior, bearing in mind the purpose of assessing retrofitting solutions.…”
Section: Introductionmentioning
confidence: 99%